Bibliometric analysis of publications trends in Indonesian research institutions: A comparison of pre-integration (2015–2021) and post-integration (2022–2023) periods - Setiowiji Handoyo; Poppy Indah Dwi Prastiti; Iwan Ridwan Stiaji (European Science Editing)
Background: Institutional transformation – integrating many disparate research insti-tutes into the National Research and Innovation Agency (BRIN, for Badan Riset dan Inovasi Nasional) – was the most significant reform in the history of institutional gov-ernance in Indonesia. This integration policy aims to enable the state to strengthen the national research and innovation ecosystem and improve the performance of research institutions, one indicator of which is their output of publications reporting the results of research. Objectives: To compare the published output of research institutes before and after the integration of research institutions into BRIN. Methods: Relevant data retrieved through Scopus on 24 December 2023 and span-ning the period between 2015 and 2023 were analysed using Microsoft Excel, and col-laboration networks of authors and of countries were constructed using VOSviewer and examined for co-authors in different countries collaborating with first authors in Indonesia. Results: The number of publications increased annually over the period 2015–2023. However, the annual rate of growth after (2021–2023) the integration of research institutions was higher (36%) than that before (2015–2021) the integration (30%). Conference papers (51%) dominated the pre-integration era, whereas articles (57%) dominated the post-integration era, and the number of reputable journals in which the research was published was greater after the integration. Conclusions: The period after the integration of research institutions saw enhanced research output in terms of the number of research publications, annual rate of growth in that number, and the number of reputable journals in which the publica-tions appeared.